Specific features of using historical and cultural resources of the Ukrainian-Polish borderland for tourism purposes - Stepan Kuzyk; Daryna Lytvyn (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The present article is dedicated to the investigation of an important part of tourist resources of the Ukrainian and Polish borderland, namely, the unique monuments of its material culture. It analyses the main historic and cultural reasons of appearing monuments on this territory, the distribution of these monuments among administrative units (rayons and poviats) with their representation on a diagram. The diagram was based on Ukraine and Polish Lists of Monuments. The article also studies the structure of the historic and cultural resources: the stationary monuments of history, architecture, city-planning, reserved castles and objects of lanscape gardening art etc.  Among all the resources it descripes monuments and architectural complexes on the UNESCO List. Also, it analyses the tourist itineraries functioning on the territory of the Ukrainian and Polish borderland. Main itineraries were taken from the tourist maps of Lviv, Volyn, Lubelskie and Podkarpackie regions. Also it proposes several new cross-border itineraries, which can potentially satisfy the  demand on meaningful rest and generating tangible revenues on this territory.